Apoptotic Potency of Bawang Dayak(Elutherine americana) Bulb Extract as Inhibitor of BPH through Computational Studies (Biological Sciences - PJSIR, 2019)
Benign Prostatic Hyperplasia (BPH) is indicated by hyperproliferation of prostate epithelial and stromal cells. Bawang Dayak (Elutherine americana) is an Indonesian endemic plant which is used as herbal medicine for BPH. This study aimed to reveal the potency of Bawang Dayak bulbs extracts as an inhibitor agent of BPH cells. The research was conducted based on in silica approach. The 3D structure of active compound and protein target were studied and analyzed molecular interaction, calculated binding affinity, and pharmacophore, visualized biomolecules, and analyzed biological activity of each active compound. They are naphthalene, naphthoquinone, and anthraquinone. All active compounds have a higher binding affinity to COX-2. It has the highest binding affinity value around -8.7 Kcal/mol. Anthraquinone has an ability as anti-inflammatory and apoptosis agonist, which blocks the COX-2 active site, so, the Bcl- 2 would be inactivated and apoptosis can occur immediately.Keywords: